Nature at Work: Ongoing Saga of Evolution - Sharma, Vinod P.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2010)
Charles Robert Darwin was born on 12th February, 1809 in Shrewsbury, England. Darwin shares his birthday with U. S. President Abraham Lincoln. Both were crusaders against slavery: Darwin disliked slavery and Lincoln abolished it. Darwin was a born naturalist and showed keen interest in nature from the very beginning. A breakthrough came when he was selected as a naturalist on the H. M. S. Beagle ship. His ?ve year voyage on the Beagle started in 1931 and was completed in 1936. This was followed by publication of his research ?ndings that challenged creationist views of the church. Darwin conducted a study of fossils and geological records and concluded rightly, that all life forms emerged over millions of years of evolution through the force of natural selection. In 1959 Darwin published his work on evolution in a book titled (3z(BOn the Origin of Species by Means of Natural Selection or the Preservation of Favored Races(3y(B. The book was received as a scienti?c bomb shell and has since changed the human understanding of life forever. Today Darwin$1 (Bs ideas on evolution provide foundation to modern biology. Darwin died of a heart attack on the 19th April 1882 and was buried in Westminster Abbey near the grave of Sir Isaac Newton. The scienti?c community is celebrating Darwin$1 (Bs bicentenary worldwide in honor of his ingenuity, scienti?c thought, conviction and courage.s
Legacy Continuum -- The descent of humans and the Darwinian unification of all life -- Ida: A link to human evolution -- Darwin$1 (Bs theory of evolution: Survival of nature$1 (Bs fit! -- The life and research of JBS Haldane in India with special reference to Charles Darwin -- Charles Darwin: A driving force for humanity toward agnosticism -- Viruses, Microbes and Fungi -- Phylogeographic evolution of plant viruses -- Evolution of HIV-1 in India -- Darwin and microbial evolution -- Evolutionary relationships among cyanobacteria, algae and plants: Revisited in the light of Darwinism -- Biodiversity, phylogeny and evolution of fungi -- Insects: Evolution in Action -- The origin of reproductive isolating mechanisms is an important event in the process of speciation: Evidences from Drosophila -- Adaptive radiation and insects -- Insights from mosquito evolution: Patterns, tempo and speciation -- The saga of pollination biology -- Genomics -- Darwinian evolution and post developments in genomics -- Pathogen pressure and molecular evolutionary genetics of innate immunity genes in humans -- Unique Case Studies -- Macroevolution in relation to the drift models of the Indian plate -- Testing the melanism-desiccation hypothesis: A case study in Darwinian evolution -- Origin and evolution of human malaria parasite, P. falciparum and P. vivax -- Evolutionary trends in soil-inhabiting alaimid nematodes -- Evolution of the cerebral cortex in amniotes: Anatomical consideration of neuronal types -- Medicinal and aromatic plants: A case example of evolving secondary metabolome and biochemical pathway diversity -- Conservation of Himalayan bioresources: An ecological, economical and evolutionary perspective.s
Keywords: Life sciences; Earth sciences; Geography; Education; Popular works; Environment; Life Sciences; Life Sciences, general; Popular Science, general; Education, general; Environment, general; Geography, general; Earth Sciences, general; Electronic books